If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x = 7x + -4 Reorder the terms: 9x = -4 + 7x Solving 9x = -4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 9x + -7x = -4 + 7x + -7x Combine like terms: 9x + -7x = 2x 2x = -4 + 7x + -7x Combine like terms: 7x + -7x = 0 2x = -4 + 0 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| 10x^2-2=-20 | | -2y-14=-10 | | -36/9= | | -(6k+8)=7k-6(k-1) | | -24+20w=73 | | -3x-16= | | (2x)/(x+1)=(2x-1)/x | | -2(3v-1)-4(v+8)=-7v-6v | | 1/2x-4=-4 | | -63(-9)= | | 7-6(c-1)+3(3-4c)= | | 21m^2+28m=0 | | 9ln(x^2)=8 | | -r=30 | | 4(1-7m)=7(1-3m)-4m | | 4(2+p)=-(2p+4) | | 4(2+p)=-2(p+4) | | 28=-14n | | 2y-w=x | | -3(6+3x)-8=-8(x+4)+7 | | 49=-7/6x | | 6(-8)= | | 6r-3(6-3r)=4(1-3r)+5 | | 2x+4(x+1)=6(x+2) | | [4y-3x-2][4y+3x+2]= | | 7.2x+6y=-3 | | 3/7=9/n | | 6r-3(6-3r)=4(1-3r+5) | | 2x+4(x+1)=6(x+2)3 | | xsqr+24+xsqr+9=5 | | -1/2(1-3)=1/3(2+1) | | [4y-3x-2y][4y+3x+2]= |